Influence of simulation on electronic health record use patterns among pediatric residents. (21st August 2018) - Orenstein, Evan W; Rasooly, Irit R; Mai, Mark V; Dziorny, Adam C; Phillips, Wanczyk; Utidjian, Levon; Luberti, Anthony; Posner, Jill; Tenney-Soeiro, Rebecca; Bonafide, Chris P
Abstract: Objective: Electronic health record (EHR) simulation with realistic test patients has improved recognition of safety concerns in test environments. We assessed if simulation affects EHR use patterns in real clinical settings. Materials and Methods: We created a 1-hour educational intervention of a simulated admission for pediatric interns. Data visualization and information retrieval tools were introduced to facilitate recognition of the patient's clinical status. Using EHR audit logs, we assessed the frequency with which these tools were accessed by residents prior to simulation exposure (intervention group, pre-simulation), after simulation exposure (intervention group, post-simulation), and among residents who never participated in simulation (control group). Results: From July 2015 to February 2017, 57 pediatric residents participated in a simulation and 82 did not. Residents were more likely to use the data visualization tool after simulation (73% in post-simulation weeks vs 47% of combined pre-simulation and control weeks, P <. 0001) as well as the information retrieval tool (85% vs 36%, P < .0001). After adjusting for residents' experiences measured in previously completed inpatient weeks of service, simulation remained a significant predictor of using the data visualization (OR 2.8, CI: 2.1-3.9) and information retrieval tools (OR 3.0, CI: 2.0-4.5). Tool use did not decrease in interrupted time-series analysis over a median of 19 (IQR: 8-32) weeks of post-simulation follow-up. Discussion: Simulation was associated with persistent changes to EHR use patterns among pediatric residents. Conclusion: EHR simulation is an effective educational method that can change participants' use patterns in real clinical settings.